Respuesta :
(-2)⁵................ => (-2)(-2)(-2)(-2)(-2)...........=> -32.
recall, minus times minus is plus, and minus times plus is minus.
Expression step by step:
[tex] { - 2}^{5} = [/tex]
[tex]( - 2 )\times ( - 2 )\times ( - 2) \times (- 2 )\times ( - 2) = [/tex]
-32
Hope it helped,
BioTeacher101
(If you have any questions feel free to ask them in the comments)
[tex] { - 2}^{5} = [/tex]
[tex]( - 2 )\times ( - 2 )\times ( - 2) \times (- 2 )\times ( - 2) = [/tex]
-32
Hope it helped,
BioTeacher101
(If you have any questions feel free to ask them in the comments)